New scoring classification for primary biliary cholangitis–autoimmune hepatitis overlap syndrome. Issue 3 (20th February 2018) - Zhang, Wei; De, Debapriya; Mohammed, Kahee A.; Munigala, Satish; Chen, Guilan; Lai, Jin‐Ping; Bacon, Bruce R.
Abstract : Autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC) are two major immune‐mediated chronic liver diseases. Overlap syndrome (OS) is diagnosed if patients have features of both AIH and PBC; however, there is no consensus on the definition or diagnostic criteria for OS. Here, we report a new scoring classification for OS and evaluate its usefulness. This new scoring classification was developed by modifying the International Autoimmune Hepatitis Group classification by selecting histologic features of AIH and PBC along with modifications of biochemical and immunologic characteristics. We evaluated 272 patients with chronic liver disease, including 105 with AIH, 102 with PBC, and 65 with OS. The best performance for the diagnosis of OS was noted among patients with an overlap score of ≥21 who had a sensitivity of 98.5%, a specificity of 92.8%, a positive predictive value of 81.0%, and a negative predictive value of 99.5%. By using a cut‐off score of 21, 64 (98.5%) patients were diagnosed with OS as opposed to 9 (8.8%) and 6 (5.7%) with PBC and AIH, respectively. All patients with OS had an aggregate score of >19, whereas most patients with PBC or AIH scored <19, making this a safe discriminatory cut‐off point against OS. Conclusion : The new scoring system for the diagnosis of OS has a high sensitivity and specificity for scores ≥21, while a score <19 suggests a diagnosis other than OS. This classification can identify patients and diagnose OS with a reasonable amount of accuracy and may be superior to current OS scoring systems in detecting mild forms of OS. ( Hepatology Communications 2018;2:245‐253)